2009
DOI: 10.1200/jco.2009.19.6410
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Pathologic Complete Responses to Neoadjuvant Chemotherapy in Diabetic Patients With Breast Cancer

Abstract: Diabetic patients with breast cancer receiving metformin and neoadjuvant chemotherapy have a higher pCR rate than do diabetics not receiving metformin. Additional studies to evaluate the potential of metformin as an antitumor agent are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
567
8
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 799 publications
(608 citation statements)
references
References 40 publications
22
567
8
11
Order By: Relevance
“…Whereas certain insulin analogues do lead to tumour development in rats, their effect in human patients remains controversial ( Refs 150,151,152). In line with the amelioration of obesity and hyperinsulinemia by metformin, observational data showed that its use was associated with a reduced risk of cancer (Refs 143,153,154). Additionally, it might also inhibit tumor progression by AMPK-mediated inhibition of mTORC1, and possibly also by a Rac GTPase-dependent and AMPK-independent mechanism (Ref.…”
Section: Metformin and Ampk In Clinical Usementioning
confidence: 99%
“…Whereas certain insulin analogues do lead to tumour development in rats, their effect in human patients remains controversial ( Refs 150,151,152). In line with the amelioration of obesity and hyperinsulinemia by metformin, observational data showed that its use was associated with a reduced risk of cancer (Refs 143,153,154). Additionally, it might also inhibit tumor progression by AMPK-mediated inhibition of mTORC1, and possibly also by a Rac GTPase-dependent and AMPK-independent mechanism (Ref.…”
Section: Metformin and Ampk In Clinical Usementioning
confidence: 99%
“…Data collected between 1991 and 1996 demonstrated that patients with type 2 diabetes mellitus exposed to sulfonylureas and exogenous insulin had significantly greater cancer-related mortality rates than did patients treated with metformin [23]. Recently, Jiralerspong and colleagues [24] compared the rates of pathological complete response (pCR) in diabetic patients with breast cancer who were receiving neoadjuvant chemotherapy and being treated with metformin or not. The rate of pCR (better outcomes) was 24% in the metformin group and 8% in the non-metformin group (p=0.007).…”
Section: Merriam-webster Dictionary 11th Edition (1977)mentioning
confidence: 99%
“…Diabetics treated with metformin have a 23% reduced risk of cancer, including breast cancer, compared to those on sulfonylureas [1] and a lower cancer-related mortality at 36 months [2]. Coincidental use of metformin in diabetics undergoing neoadjuvant chemotherapy for breast cancer resulted in a higher pathological complete response (24%), compared to diabetics not on metformin (8%) or non-diabetic patients (16%) [3].…”
Section: Introductionmentioning
confidence: 99%